Why Education Predicts Decreased Belief in Conspiracy Theories - Prooijen, Jan‐Willem (Applied cognitive psychology, 2017)
Summary People with high education are less likely than people with low education to believe in conspiracy theories. It is yet unclear why these effects occur, however, as education predicts a range of cognitive, emotional, and social outcomes. The present research sought to identify mediators of the relationship between education and conspiracy beliefs. Results of Study 1 revealed three independent mediators of this relationship, namely, belief in simple solutions for complex problems, feelings of powerlessness, and subjective social class. A nationally representative sample (Study 2) replicated these findings except for subjective social class. Moreover, variations in analytic thinking statistically accounted for the path through belief in simple solutions. I conclude that the relationship between education and conspiracy beliefs cannot be reduced to a single mechanism but is the result of the complex interplay of multiple psychological factors that are associated with education. © 2016 The Authors. Applied Cognitive Psychology published by John Wiley & Sons Ltd.